Map of North America. - Johnson, A. J. (Alvin Jewett), 1827-1884 ([A.J. Johnson & Co.], 1889)
Map shows late nineteenth century North America coal fields, major cities, railroads; state, province, and territory boundaries; Nicaragua and Panama canals. Includes text notes about arctic expeditions. Relief shown by hachures. Scale [ca. 1:28,160,000].